The orchestration of dynamic capabilities in cleantech companies - Matheus Eurico Soares de Noronha; Diandra Maynne Ferraro; Leonardo Reis Longo; Scarlet Simonato Melvin (Innovation & Management Review, 2024)
Purpose The aim of this article is to present a model for the orchestration of dynamic capabilities (ODCs) in cleantech companies that aim to obtain competitive advantage in the market. Design/methodology/approach The authors present herein descriptive research guided by a qualitative multiple case study approach carried out with 12 cleantech companies. Findings The results have showed that the ODC model is present in the product/process cycle, thus providing new capabilities and generating sustainable competitive advantage through the research categories presented. Research limitations/implications This study contributes to the literature on the ODCs through microfoundations based on evidence of companies inserted in technological and intensively dynamic contexts. Practical implications This article demonstrates, through the ODC model, the main capabilities and characteristics of the assets of cleantech companies and how the process of renewing competencies to obtain competitive advantage occurs. Originality/value The ODC model utilizes technological resources in the product/process cycle. Asset specificity and the capacity for innovation allow cleantech companies to explore regulatory loopholes, making their sustainable model innovative and obtaining competitive advantage through the renewal of entrepreneurial capabilities and competencies.
Keywords: 650; Cleantech; Dynamic capabilities; Orchestration of dynamic capabilities